Dynamic business law : (McGraw-Hill/Irwin, 2013)
Emphasis on the business in business law. Dynamic Business Law emphasizes the tie of legal issues back to the core business curriculum. This will help both students and faculty. Students need to understand how the concepts they learn in this course tie into their business careers. Instructors can easily show that the study of business law is best seen as a foundational component of the larger study of business administration. Emphasis on teaching. We know that many of you teaching this course are practicing attorneys, have little prep time for this course, and often don't have a lot of resources at your disposal or teach the course as effectively as you might like. Dynamic Business Law is written with you in mind. It contains a very detailed and helpful instructor's manual, particularly for the many adjuncts teaching this course. And most importantly, the author team has won dozens of teaching awards, both state and national, and they are dedicated to help you get started using this book.